2012
DOI: 10.1176/appi.ps.201100422
|View full text |Cite
|
Sign up to set email alerts
|

England's Time to Change Antistigma Campaign: One-Year Outcomes of Service User-Rated Experiences of Discrimination

Abstract: Results suggest positive progress toward meeting the program's targeted 5% reduction in discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 23 publications
3
50
1
Order By: Relevance
“…The survey supported previous findings in relation to discrimination by family; over half of respondents reported discrimination from their family because of their diagnosis (Henderson et al, 2012).…”
Section: Familysupporting
confidence: 88%
See 1 more Smart Citation
“…The survey supported previous findings in relation to discrimination by family; over half of respondents reported discrimination from their family because of their diagnosis (Henderson et al, 2012).…”
Section: Familysupporting
confidence: 88%
“…Studies show that mental health discrimination is identified most frequently as occurring in interpersonal interactions with family being consistently reported as a primary source of discriminatory behaviours (Corker et al, 2013;Henderson et al, 2012;Lasalvia et al, 2012;Thornicroft & Kennedy, 2009). This may be due, in part, to high levels of social exclusion, resulting in more social contact with family members than other potential sources (Angermeyer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We think this highlights the fallacy whereby clinicians may make unfavorable assumptions about the level of functioning of people with borderline personality disorder during their daily lives based on their presentation during a crisis. Our findings also demonstrate that the same issues of dignity, respect, and autonomy identified in global surveys of discrimination among people with severe mental illness (42,43) are important to people with borderline personality disorder. Our findings have important implications for clinicians involved in the daily care of people with borderline personality disorder, at a time in the evolution of health care services when shared decision making (44) is becoming the norm rather than the exception.…”
Section: Discussionsupporting
confidence: 66%
“…The CWBS is also the first study to assess the pervasiveness of self-stigma (i.e., negative feelings about one's own mental illness) and experiences of mental illness-related discrimination using a sample that is representative of individuals who are at risk for or are experiencing mental health problems. In contrast, previous studies examining mental illness stigma and discrimination among individuals experiencing mental health challenges have been largely limited to individuals recruited from mental health service or advocacy organizations (Brohan et al, 2011;Henderson et al, 2012), which may yield biased estimates given that a large percentage of the broader population of individuals affected by mental health challenges do not engage in treatment.…”
Section: Key Findingsmentioning
confidence: 99%